The calming effect of maternal carrying in different mammalian species - Esposito, Gianluca; Setoh, Peipei; Yoshida, Sachine; Kuroda, Kumi O. (Frontiers in Psychology, 2015)
Attachment theory postulates that mothers and their infants possess some basic physiological mechanisms that favour their dyadic interaction and bonding. Many studies have focused on the maternal physiological mechanisms that promote attachment (e.g. mothers’ automatic responses to infant faces and/or cries), and relatively less have examined infant physiology. Thus, the physiological mechanisms regulating infant bonding behaviors remain largely undefined. This review elucidates some of the neurobiological mechanisms governing social bonding and cooperation in humans by focusing on maternal carrying and its beneficial effect on mother-infant interaction in mammalian species (e.g. in humans, big cats and rodents). These studies show that infants have a specific calming response to maternal carrying. A human infant carried by his/ her walking mother exhibits a rapid heart rate decrease, and immediately stops voluntary movement and crying compared to when he/ she is held in a sitting position. Furthermore, strikingly similar responses were identified in mouse rodents, who exhibit immobility, diminished ultra-sonic vocalizations and heart rate. In general, the studies described in the current review demonstrate the calming effect of maternal carrying to be comprised of a complex set of behavioral and physiological components, each of which has a specific postnatal time window and is orchestrated in a well-matched manner with the maturation of the infants. Such reactions could have been evolutionarily adaptive in mammalian mother-infant interactions. The findings have implications for parenting practices in developmentally normal populations. In addition, we propose that infants’ physiological response may be useful in clinical assessments as we discuss possible implications on early screening for child psychopathology (e.g. Autism Spectrum Disorders, and Perinatal Brain Disorders).